Making Sense of the Dark: A Study on the Identity of Men Who Committed Homicide. Issue 2 (14th March 2020) - Ferrito, Martha; Needs, Adrian; Jingree, Treena; Pearson, Dominic
ABSTRACT: Identities change after major interpersonal events. However, there is comparatively little study of what identity change means after the commission of an act of severe interpersonal violence, such as homicide. Individual in-depth interviews with men who had taken a life were conducted, looking at the experience of living with and making sense of their offense. The interviews were transcribed verbatim and examined using Interpretative Phenomenological Analysis (IPA). The findings identified two themes: "The Reformed Self-Identity" and "Factors that contribute to a Reformed Self-Identity". The first theme examines the new reformed identity and the second theme explores the factors that have helped the participants to make sense of the trajectory of their experiences. This study reports on identity work as predominantly an intersubjective process, where the making of the self is influenced by their relations with others. Positive contextual influences (e.g., family support, engagement in therapy) in cultivating reconciliations in identity, meaning, and reflexive connections are vital aspects in informing meaning-based therapeutic interventions and rehabilitative aims (including risk reduction and accountability). The reduction in future risk, which links in with the relationship between social inclusion and self-regulation, reducing the need to compensate for shame and the implications of shifts in identity and meaning was another important point that emerged from this study. Furthermore, this study highlights the importance of reflective spaces for perpetrators of homicide to engage with the impact of their index offenses, in order to be able to support a new identity and a new life with safe and accountable connections.